Implementación del sistema de protecciones eléctricas para una estación fotovoltaica de autoconsumo de 500 w - Coyachamin Chiliquinga, Jhonatan Alexander (2022)
The technological proposal is aimed at implementing a system that allows protecting the human being and increasing the useful life of the elements and equipment of the photovoltaic system since they need to have electrical protection because they can generate overloads and short circuits because they can cause electrical risks due to lack of of protections of the same, this system is implemented in the renewable energy laboratory of the Technical University of Cotopaxi in the city of Latacunga, through field research, information was collected from the existing plates of each of the teams that make up This system to determine the values ​​of voltage and currents that are generated in them and applying the current ARCONEL regulation of protections allows us to size each one of the protections according to the capacity of the electrical magnitudes. Whose sizing is based on the maximum dissipation power of each of the equipment that make up the photovoltaic system itself that allows me to obtain the characteristic curves of the protection system.